방사선 근접치료의 디지털 정도관리를 위한 Lead (Ⅱ) Oxide 선량계 성능 평가 - 한무재; Moo-jae Han; 양승우; Seung-woo Yang; 박성광; Sung-kwang Park (한국방사선학회 논문지, 2021)
방사선 근접치료에서 잘못된 선원의 위치는 정상조직에 과도한 선량을 유발할 수 있기 때문에 선원의 위치 정확성 평가는 필수적이다. 이에 본 연구에서는 기존 아날로그 검증방식을 개선시키기 위해 lead (Ⅱ) oxide (PbO) 기반의 디지털 선량계에 대한 기초연구를 수행하였다. 이에 다결정 PbO 선량계를 제작하였고 Ir-192 선원에 대한 계측 성능을 평가하였다. 그 결과 재현성은 상대표준편차가 0.82%로 평가 기준 1.5% 이내를 만족하였다. 선형성은 선형함수 R 2 이 0.9998로 우수한 결과를 보였다. 거리 의존성 평가의 경우, 거듭제곱함수 R 2 은 PbO에서 0.9855, diode에서 0.9974를 보였고, 전체 평균차이는 PbO에서 1.66%, diode에서 2.18% 차이를 보였다. 본 연구는 다결정 PbO 선량계의 Ir-192 선원에 대한 기초 검출성능을 제시하며, 방사선 계측분야에서 기초자료를 제공할 수 있다. In intracavitary radiotherapy, incorrect location of the source can cause excessive dose to normal tissue, so it is essential to evaluate the location accuracy of the source. In this study, basic research was performed on digital line dosimeter based on lead (Ⅱ) oxide (PbO) to improve analog verification method. Therefore, a polycrystalline PbO unit cell dosimeter was manufactured and the measurement performance for Ir-192 sources was evaluated. As a result, the reproducibility satisfies the evaluation criteria of 1.5% with a relative standard deviation of 0.85%. Linearity showed excellent results with a linear coefficient of R 2 of 0.9998. In the case of distance dependence evaluation, the power function R 2 showed 0.9855 for PbO and 0.9974 for diode, and the overall average difference was 1.66% for PbO and 2.18% for diode. This study presents the basic detection performance of the polycrystalline PbO dosimeter for the Ir-192 source and can provide basic data in the field of radiation measurement.